Dairy intake during adolescence and risk of colorectal adenoma later in life - Nimptsch, Katharina; Lee, Dong Hoon; Zhang, Xuehong; Song, Mingyang; Farvid, Maryam S.; Rezende, Leandro F. M.; Cao, Yin; Chan, Andrew T.; Fuchs, Charles; Meyerhardt, Jeffrey; Nowak, Jonathan A.; Willett, Walter C.; et al. (British journal of cancer, 2021)
Background Higher dairy intake during adulthood has been associated with lower colorectal cancer risk. As colorectal carcinogenesis spans several decades, we hypothesised that higher dairy intake during adolescence is associated with lower risk of colorectal adenoma, a colorectal cancer precursor. Methods In 27,196 females from the Nurses’ Health Study 2, aged 25–42 years at recruitment (1989), who had completed a validated high school diet questionnaire in 1998 and undergone at least one lower bowel endoscopy between 1998 and 2011, logistic regression for clustered data was used to calculate odds ratios (ORs) and 95% confidence intervals (CI). Results Colorectal adenomas were diagnosed in 2239 women. Dairy consumption during adolescence was not associated with colorectal adenoma risk (OR highest vs. lowest [≥4 vs. ≤1.42 servings/day] quintile [95% CI] 0.94 [0.80, 1.11]). By anatomical site, higher adolescent dairy intake was associated with lower rectal (0.63 [0.42, 0.95]), but not proximal (1.01 [0.80, 1.28]) or distal (0.97 [0.76, 1.24]) colon adenoma risk. An inverse association was observed with histologically advanced (0.72 [0.51, 1.00]) but not non-advanced (1.07 [0.86, 1.33]) adenoma. Conclusions In this large cohort of younger women, higher adolescent dairy intake was associated with lower rectal and advanced adenoma risk later in life.